Belize : Staff Report for the 2006 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Overly expansionary macroeconomic policies contributed to a widening of current account deficits, an unsustainable buildup of public debt, and the erosion of international reserves. The Belize government has already made commendable strides in correcting macroeconomic imbalances, based on measures to increase tax collection, rein in discretionary current expenditure, and cut capital expenditure. However, these efforts alone are not sufficient to bring the public finances and the balance of payments back on a sustainable path; supportive structural reforms in the fiscal and monetary areas should be implemented.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet